2013
DOI: 10.1515/jpem-2012-0390
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D loading doses on serum 25-hydroxy vitamin D levels in school going adolescents: an open label non-randomized prospective trial

Abstract: Supplementing 60,000 IU of vitamin D3 per week for 4-8 weeks, followed by 600 IU daily through fortified milk, is an effective strategy for achieving vitamin D sufficiency in Indian adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 12 publications
4
35
1
Order By: Relevance
“…4 Khadgawat et al, Garg et al and various other studies have also reported a high prevalence of vitamin D deficiency in Indian population. [6][7][8][9][10][11][12][13] In the present study, we found that after supplementation with vitamin D, the weight SD score of children increased significantly. This is due to direct influence of vitamin D levels on weight of the children.…”
Section: Discussionmentioning
confidence: 75%
“…4 Khadgawat et al, Garg et al and various other studies have also reported a high prevalence of vitamin D deficiency in Indian population. [6][7][8][9][10][11][12][13] In the present study, we found that after supplementation with vitamin D, the weight SD score of children increased significantly. This is due to direct influence of vitamin D levels on weight of the children.…”
Section: Discussionmentioning
confidence: 75%
“…In India, studies from different parts of the country have reported a high prevalence of VDD 96.9% (adolescents),[9] 90.8% (6–18 years),[10] 93.7% (school girls),[11] 92.3% (10–14 years)[12] and 87% (college students),[13] respectively. The cut-offs to define VDD, however, varied between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[8910111213] Majority of these studies have been conducted in plain regions of country. The common risk factors identified as associated with VDD are low exposure to sun,[14] atmospheric pollution,[15] darker skin pigmentation,[16] low physical activity,[17] indoor confinement of children during the day and high rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not evaluate subjects for hypercalciuria using urinary calcium measurement, most recent studies from India and Turkey have failed to show any significant hypercalciuria in Vitamin D treated subjects. [3233]…”
Section: Discussionmentioning
confidence: 99%